National policy actions on dementia in the Americas and Asia-Pacific: Consensus and challenges - Fei Sun; Emmanuel Chima; Tracy Wharton; Vijeth Iyengar (Pan American Health Organization, 2020)
Alzheimer's disease and related dementias (ADRD) affect over 50 million persons globally, and the number is expected to rise. In response, health ministries are developing and implementing policies and programs to systemically address the needs of individuals and families affected by ADRD. While national plans of action on ADRD are advancing among European Member States of World Health Organization (WHO), those in the Asia-Pacific and Americas are lagging behind. Since previous studies have largely ignored the Americas and Asia-Pacific-where approximately two-thirds of the global ADRD population resides-this study sought to identify (a) the socioeconomic factors associated with the likelihood of having a national dementia policy, and (b) to examine common and differing features among the national plans in these regions. Employing the dementia policy guidelines of WHO and the Pan American Health Organization as an extraction guide for data collection and analysis, the national dementia plans and available socioeconomic data of 10 Member States were analyzed with comparative and qualitative analyses. Findings suggested at least a 14-fold increase in the likelihood of having a national dementia plan if a Member State had one of the following: a universal health care system, more than 14% of the population 65 years of age or older, or high-income. All the Member States in the study identified dementia as a public health priority, but priorities differed. Inconsistencies included development of information systems, training for health care professionals, and long-term care systems.